Accepting Lower Salaries for Meaningful Work - Hu, Jing; Hirsh, Jacob B. (Frontiers in Psychology, 2017)
A growing literature indicates that more and more people are highly motivated to experience a sense of meaning in their work lives. Little is known, however, about how the perception of work meaningfulness influences job choice decisions. Although much of the research on job choice has focused on the importance of financial compensation, the subjective meanings attached to a potential job should also play a role. The current set of studies explored the hypothesis that people are willing to accept lower salaries for more meaningful work. In Study 1, participants reported lower minimum acceptable salaries when comparing jobs that they considered to be personally meaningful with those that they considered to be meaningless. In Study 2, an experimental enhancement of a job’s apparent meaningfulness lowered the minimum acceptable salary that participants required for the position. In two large-scale cross-national samples of full-time employees in 2005 and 2015, Study 3 found that participants who experienced more meaningful work lives were more likely to turn down higher-paying job offers elsewhere. The strength of this effect also increased significantly over this time period. Study 4 replicated these findings in an online sample, such that participants who reported having more meaningful work were less willing to leave their current jobs and organizations for higher paying opportunities. These patterns of results remained significant when controlling for demographic factors and differences in job characteristics.